Pengaruh Kompetensi, Motivasi Kerja, dan Kepuasan Kerja Terhadap Produktivitas Kerja Pegawai Kantor Badan Pertanahan Nasional Kabupaten Sampang - Hatami, Muhammad; Salim, Muhammad Agus; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Work productivity reflects the effectiveness and efficiency of human resource performance. This study analyzes the impact of competence, work motivation, and job satisfaction on employee productivity at the Badan Pertanahan Nasional (BPN) Office in Kabupaten Sampang, driven by a decline in productivity marked by tardiness and low initiative. Using a quantitative explanatory design, data were collected from 34 employees through questionnaires and analyzed using multiple linear regression with simultaneous and partial hypothesis testing.The results indicate that competence, motivation, and job satisfaction together significantly affect productivity, but only competence has a partial significant impact. Competence covering knowledge, skills, and attitude supports task performance. Although motivation and satisfaction contribute to a positive work environment, they show no direct effect. These findings emphasize the need for holistic HR management focused on competence development and employee well-being to enhance productivity and service quality. Keywords: Competence, Work Motivation, Job Satisfaction, Work Productivity, Human Resources.